Linguistic Technopreneurship in Business Success Digitalization for Small Medium Enterprises in West Java: Implication for Language Education - Suprayogi, Yogi; Luckyardi, Senny; Kurnia, Dede; Khairusy, Mirza Abdi (International Journal of Language Education, 2024)
The increase in borderless digital-based business competition shows how language education is impacted by neoliberalism in this global era. We explore how linguistic technopreneurship (LT) roles is increasingly constructed as a form of linguistic entrepreneurship to exploit language-related resources to enhance one's socioeconomic value strategically. This research aims to critically examine the influence of LT toward business success digitalization for Small Medium Enterprises in West Java  and it’s implication for Language Education. The research also focusing on the creation of novelty, namely linguistic technopreneurship (LT), which is a refinement of entrepreneurial linguistics (EL). LT is expected to be able to explain how linguistic entrepreneurship can be indexed from two different aspects, namely how to package language education and digital business success. We then discuss under what conditions the notion of linguistic technopreneurship can be applied to digital platform-based business settings and what kind of contradictions this gives rise to. The method used is quantitative, and it involves carrying out SEM analysis. A non-probability sampling technique was used to obtain a minimum of 250 Micro, Small and Medium Enterprises and Industry owners who run their businesses through digital platforms in West Java province, which is the province with the most significant number of Micro, Small and Medium Enterprises and Industries in Indonesia. The research results show that LT significantly influences the success of business success and impact the language education practice. It can be concluded that language education is an added value for a person and influences socioeconomic success.